CS-37 Prevalence of cognitive impairment in systemic lupus erythematosus assessed by a comprehensive neuropsychological battery. (August 2018) - Touma, Zahi; Green, Robin; Engel, Lisa; Tartaglia, Carmela; Ruttan, Lesley; Lombardi, Sabrina; Anderson, Nicole; Su, Jiandong; Colosimo, Kenneth; Vitti, Michelle; Bonilla, Dennise; Wither, Joan; et al.
Abstract : Background: Cognitive impairment (CI) is a common neurobehavioural manifestation of systemic lupus erythematosus (SLE). In our recent systematic review, the prevalence of CI was 38% (95% CI 33% to 43%) with a wide variation (15%–79%), which may be due to differences in CI definitions and selection of neuropsychological tests across studies. We aim to report the prevalence of CI in a large cohort using a comprehensive battery (CB) of tests in which we operationalized the classification of CI. Methods: Consecutive consenting SLE patients, aged 18–65 years, who attended a single center (Jul 2016-Feb 2018) were recruited. Patients were administered a CB that evaluates the major cognitive domains: Manual motor speed and dexterity, simple attention and processing speed, visual-spatial construction, verbal fluency, learning and memory (visuospatial and memory), executive functioning (untimed and timed). Patient scores were compared to a normative sample of age- and gender-matched healthy controls to obtain z-scores. CI was operationalized on the CB as a z-score of ≤−1.5 (as compared to controls) on ≥2 domains or z≤−2.0 on ≥1 domain. Descriptive statistics were used. Results: Of the 199 patients (89% female), the mean age at SLE diagnosis was 28.3±10.4 and disease duration at enrolment was 14.3±10.2 years. The prevalence of CI was 37.7% (z≤−1.5 in ≥2 domains) and 49.8% (z≤−2.0 in ≥1 domains). Prevalence of patients with domain z-scores of ≤−1.5 and ≤−2.0 varied from 3.0%–46.2% and 0.5%–25.1% respectively (figure 1). The most affected domain was learning and memory (visuospatial and memory) in 92 (46.2%) patients based on z≤−1.5 on ≥2 subtests and 50 (25.1%) patients based on z≤−2.0 in ≥1 subtest. Conclusion: Prevalence of CI using our CB ranged between 37.7%–49.8% (z≤−1.5 in≥2 domains and z≤−2.0 in≥1 domains respectively), which was higher than the pooled prevalence from previous reports of 38%. These differences in CI prevalence across studies could be attributed to different factors including the heterogeneity in patients' demographics/comorbidities, sample size, the use of different metrics to determine CI, and the lack of a standardized definition of CI. Further studies are required to identify the best definition for CI and its metrics. Acknowledgment: This project is funded by the Arthritis Society and the Physicians' Services Incorporated Foundation.